Using the Health Belief Model to explore rural maternal utilisation of skilled health personnel for childbirth delivery: a qualitative study in three districts of the Eastern Region of Ghana - Jeanette R Nelson; Lisa H Gren; Ty T Dickerson; L Scott Benson; Stephen O Manortey; Rebecca Ametepey; Yvette E Avorgbedor; Stephen C Alder (Inishmore Laser Scientific Publishing Ltd, 2021)
# Background Although maternal mortality has decreased substantially since the 1990s, it remains one of the top priorities in global health, as most deaths can be prevented if women have access to and utilise skilled health personnel for childbirth delivery. While efforts have been made to increase the supply and accessibility of services, the lack of maternal utilisation of skilled health delivery services is a contributing cause of death, particularly among mothers from rural areas. # Methods We conducted interviews in December 2019 in the Eastern Region of Ghana, with 24 rural mothers who had given birth within the past two years, 12 women who had and 12 women who had not given birth utilising skilled health personnel. # Results The main differences between women who did and did not use skilled health personnel for delivery were for Health Belief Model constructs of perceived risk, self-efficacy, and cues to action. Most women who delivered with skilled health personnel believed they were susceptible to complications during childbirth, reported high perceived self-efficacy to overcome barriers to deliver with skilled health personnel, and planned and prepared in advance to deliver with skilled health personnel. In contrast, women who did not deliver with skilled health personnel were less likely to believe in susceptibility to complications, reported low perceived self-efficacy to overcome barriers, and had not planned or prepared in advance for skilled health delivery. # Conclusions There were substantial differences between rural mothers who did and did not deliver with skilled health personnel regarding perceived susceptibility to experience complications, self-efficacy to overcome barriers and cues to action to prepare for birth.